Identifikasi Bakteri Salmonella Sp. Pada Bakso Kuah Di Kelurahan Bumi Ayu Kota Bengkulu - Denis, Rica; Hepiyansori (Jurnal Vokasi Kesehatan, 2024)
Food is divided into two categories, namely vegetable food and animal food. In Indonesia, there are many animal foods processed, such as meat, because it contains high protein. One of the processed meats is meatball soup. Meatball soup is much loved by people who sometimes no longer pay attention to food hygiene, which triggers various diseases such as diarrhoea caused by bacteria, one of which is Salmonella sp. This study aims to determine whether there is Salmonella sp. bacterial contamination in meatball soup sold in Bumi Ayu Village, Bengkulu City. This type of research is descriptive and uses experimental research methods, such as purposive sampling. Data analysis was carried out through a qualitative observation test. Samples were examined at the microbiology laboratory of the Harapan Bangsa Health Analyst Academy. According to the results of the study obtained from the four samples of meatball soup, two samples were contaminated by Salmonella bacteria, namely sample 2 and sample 3, while sample 1 and sample 4 were not contaminated by Salmonella bacteria.